C16 Peptide and Ang-1 Improve Functional Disability and Pathological Changes in an Alzheimer's Disease Model Associated with Vascular Dysfunction - Xiaoxiao Fu; Jing Wang; Huaying Cai; Hong Jiang; Shu Han (MDPI AG, 2022)
Alzheimer's disease (AD) is a neurological disorder characterized by neuronal cell death, tau pathology, and excessive inflammatory responses. Several vascular risk factors contribute to damage of the blood-brain barrier (BBB), secondary leak-out of blood vessels, and infiltration of inflammatory cells, which aggravate the functional disability and pathological changes in AD. Growth factor angiopoietin-1 (Ang-1) can stabilize the endothelium and reduce endothelial permeability by binding to receptor tyrosine kinase 2 (Tie2). C16 peptide (KAFDITYVRLKF) selectively binds to integrin ανβ3 and competitively inhibits leukocyte transmigration into the central nervous system by interfering with leukocyte ligands. In the present study, 45 male Sprague-Dawley (SD) rats were randomly divided into three groups: vehicle group, C16 peptide + Ang1 (C + A) group, and sham control group. The vehicle and C + A groups were subjected to two-vessel occlusion (2-VO) with artery ligation followed by Aβ1-42 injection into the hippocampus. The sham control group underwent sham surgery and injection with an equal amount of phosphate-buffered saline (PBS) instead of Aβ1-42. The C + A group was administered 1 mL of drug containing 2 mg of C16 and 400 µg of Ang-1 daily for 2 weeks. The sham control and vehicle groups were administered 1 mL of PBS for 2 weeks. Our results showed that treatment with Ang-1 plus C16 improved functional disability and reduced neuronal death by inhibiting inflammatory cell infiltration, protecting vascular endothelial cells, and maintaining BBB permeability. The results suggest that these compounds may be potential therapeutic agents for AD and warrant further investigation.